2018
DOI: 10.1111/jsr.12654
|View full text |Cite
|
Sign up to set email alerts
|

Reference values and changes in infant sleep–wake behaviour during the first 12 months of life: a systematic review

Abstract: This paper is a systematic review on the reference values and changes in infant sleep-wake behaviour during the first 12 months of life. This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Seventy-four papers were included, and the reference values and changes in sleep-wake behaviour during the first 12 months of life were identified. Sleep duration during the 24-h period, and day and sleep periods during the night decreased over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 84 publications
(154 reference statements)
4
15
1
Order By: Relevance
“…These latter studies from England [5], European countries (excluding France) [31] and the United States [32] as well as a systematic review [30] reported total sleep durations between 12h40min and 13h/24h at about age 1 year, so French parents report that their infants sleep 30-60min/24h more than their counterparts in developed countries. In a recent literature review of sleep in the first 12 months of life, sleep duration per 24 h tended to be longer in European countries than in the United States, New Zealand, Israel and China [33]. In the current study, this difference seems to be mainly due to longer nap duration in French children but similar nightsleep duration as their peers.…”
Section: Total Sleep Durationcontrasting
confidence: 41%
“…These latter studies from England [5], European countries (excluding France) [31] and the United States [32] as well as a systematic review [30] reported total sleep durations between 12h40min and 13h/24h at about age 1 year, so French parents report that their infants sleep 30-60min/24h more than their counterparts in developed countries. In a recent literature review of sleep in the first 12 months of life, sleep duration per 24 h tended to be longer in European countries than in the United States, New Zealand, Israel and China [33]. In the current study, this difference seems to be mainly due to longer nap duration in French children but similar nightsleep duration as their peers.…”
Section: Total Sleep Durationcontrasting
confidence: 41%
“…Infants spent an average of 47.50% of their waking hours engaged in screen‐time‐or‐limited physical activity and a substantial fraction (35.5%) of infants in our study engaged in some screen‐based sedentary behavior. In our study, infant daily hours of sleep were inversely related to diary‐derived screen‐time‐or‐limited physical activity, and the amount of daily sleep (10.85 hr), was similar to the 10.4 hr reported for infants 6 months of age in a systematic review (Dias et al, ). This finding suggests that reducing screen‐time‐or‐limited physical activity, including television viewing and screen time, may improve infant sleep.…”
Section: Discussionsupporting
confidence: 87%
“…These variables were chosen because they encompass clinically important dimensions of physical activity as well as sleep quantity and quality in young children. These variables have also been reported in prior pediatric research, which facilitates the interpretation of our results (Dias et al, ; Williams et al, ).…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The Panel notes that the observed differences in sleep duration or night wakings in the RCT by Perkin et al. () were small in relation to an overall night time sleep duration of around 10–11 h at 6 months of age (Dias et al., ) and that the severity of sleep problems was based on the perception of the parents. The Panel considers that the results on these three endpoints are unlikely to be of biological relevance.…”
Section: Assessment Of the Data On Sleep‐related Endpoints In Individmentioning
confidence: 99%